Characterization of Vibrio cgolerae non-O1 serogroups obtained from an outbreak of diarrhea in Lima, Peru. - Dalsgaard, A (1995)
In February 1994, an outbreak of diarrhea caused by non-O1 Vibrio cholerae occurred among volunteers in a vaccine trial study area in Lima, Peru. Clinically, 95% of the patients presented with liquid diarrhea with either no or mild dehydration. Serogrouping of 58 isolates recovered from diarrheal patients affected in the outbreak revealed seven different serogroups, with serogroups O10 (21%) and O12 (65%) being predominant. Most of these isolates were susceptible to a variety of antimicrobial agents. None of the 58 isolates hybridized with a DNA probe previously used to detect the gene encoding the heat-stable enterotoxin NAG-ST or produced cholera toxin as assessed by GM1 ganglioside enzyme-linked immunosorbent assay. Ribotyping exhibited 10 different BglI ribotype patterns among the 58 V. cholera non-O1 strains studied. However, ribotyping showed that all isolates belonging to serogroup O12 exhibited identical ribotypes and that 83% of the serogroup O10 isolates belonged to another identical ribotype, thus showing excellent correlation between ribotypes and serogroups. Among a group of O10 and O12 isolates selected for virulence studies, none produced enterotoxin whereas the majority produced a cytotoxin, as assessed in Y1 and HeLa cells. These isolates were also negative for the gene encoding zonula occludens toxin (Zot) as assessed by a PCR assay. The isolates tested showed strong adherence and some degree of invasion in the HEp-2 cell assay, whereas none of the isolates was positive in the PCR assay for the gene encoding the toxin coregulated pilus subunit A antigen (tcpA).(ABSTRACT TRUNCATED AT 250 WORDS)